Evaluating lower limb kinematics and pathology with dynamic CT: a narrative review. (1st May 2021) - Buzzatti, Luca; Keelson, Benyameen; Vanlauwe, Johan; Buls, Nico; De Mey, Johan; Vandemeulebroucke, Jef; Cattrysse, Erik; Scheerlinck, Thierry
Abstract : Evaluating musculoskeletal conditions of the lower limb and understanding the pathophysiology of complex bone kinematics is challenging. Static images do not take into account the dynamic component of relative bone motion and muscle activation. Fluoroscopy and dynamic MRI have important limitations. Dynamic CT (4D-CT) is an emerging alternative that combines high spatial and temporal resolution, with an increased availability in clinical practice. 4D-CT allows simultaneous visualization of bone morphology and joint kinematics. This unique combination makes it an ideal tool to evaluate functional disorders of the musculoskeletal system. In the lower limb, 4D-CT has been used to diagnose femoroacetabular impingement, patellofemoral, ankle and subtalar joint instability, or reduced range of motion. 4D-CT has also been used to demonstrate the effect of surgery, mainly on patellar instability. 4D-CT will need further research and validation before it can be widely used in clinical practice. We believe, however, it is here to stay, and will become a reference in the diagnosis of lower limb conditions and the evaluation of treatment options. Cite this article: Bone Joint J  2021;103-B(5):822–827.